Large Stokes Shift and High Efficiency Luminescent Solar Concentrator Incorporated with CuInS2/ZnS Quantum Dots - Li, Chen (2016)
Luminescent solar concentrator (LSC) incorporated with quantum dots (QDs) have been widely regarded as one of the most important development trends of cost-effective solar energy. In this study, for the first time we report a new QDs-LSC integrated with heavy metal free CuInS2/ZnS core/shell QDs with large Stokes shift and high optical efficiency. The as-prepared CuInS2/ZnS QDs possess advantages of high photoluminescence quantum yield of 81% and large Stocks shift more than 150 nm. The optical efficiency of CuInS2/ZnS QDs-LSC reaches as high as 26.5%. Moreover, the power conversion efficiency of the QDs-LSC-PV device reaches more than 3 folds to that of pure PMMA-PV device. Furthermore, the PV device is able to harvest 4.91 folds solar energy with the assistance of this new CuInS2/ZnS QDs-LSC for the same size c-Si PV cell. The results demonstrate that this new CuInS2/ZnS QDs-LSC provides a promising way for the high efficiency, nonhazardous and low cost solar energy.